Rats exhibit similar biases in foraging and intertemporal choice tasks - Gary A Kane; Aaron M Bornstein; Amitai Shenhav; Robert C Wilson; Nathaniel D Daw; Jonathan D Cohen (eLife, 2019)
Animals, including humans, consistently exhibit myopia in two different contexts: foraging, in which they harvest locally beyond what is predicted by optimal foraging theory, and intertemporal choice, in which they exhibit a preference for immediate vs. delayed rewards beyond what is predicted by rational (exponential) discounting. Despite the similarity in behavior between these two contexts, previous efforts to reconcile these observations in terms of a consistent pattern of time preferences have failed. Here, via extensive behavioral testing and quantitative modeling, we show that rats exhibit similar time preferences in both contexts: they prefer immediate vs. delayed rewards and they are sensitive to opportunity costs of delays to future decisions. Further, a quasi-hyperbolic discounting model, a form of hyperbolic discounting with separate components for short- and long-term rewards, explains individual rats’ time preferences across both contexts, providing evidence for a common mechanism for myopic behavior in foraging and intertemporal choice.